Identifikasi lokasi untuk pengembangan budidaya keramba jaring apung (KJA) berdasarkan faktor lingkungan dan kualitas air di perairan pantai timur Bangka Tengah - Junaidi M. Affan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Waters of the east coast of Bangka Regency has higher potency for development of mariculture livelihood. The Geographic Information Systems (GIS) can be used to determine the suitable location for these activities. Spatial analysis on every measured parameters were conducted and then its overlay to determine the feasibility of locations. The suitability location was categorized into four levels i.e very suitable, moderately suitable, suitable with conditions, and not suitable. The results showed that there are at least 127,746 ha of areas have potency for mariculture location, of these 122,950 ha (96.25%) are very suitable and suitable, while 4796 ha (3.75%) are moderately suitable for fish farming. However, based on field verification, about 8.627 ha of areas are recommended for fish mariculture developement, this is situated at Pulau Ketawai Island, Pulau Panjang dan Pulau Bujur.Key Words : Geographic Information Systems, overlay, fish, mariculture, and cage